On a One-dimensional Model of the Fracture Process - M. Sokołowski (Engineering Transactions)
An elastic tod is extracted from an elastic foundation by means of a longitudinal force applied to the free end of the rod (Fig. 1). In spite of the extreme simplicity of the model (axial forces in the rod, the foundation transmits only shearing stresses), the process reveals close analogy with the phenomena of fracture (crack propagation) in three-dimensional elastic solids. Several aspects of that analogy are discussed: the possible fracture criteria, steady-state motion of the rod extracted from the medium at a constant velocity, sudden start and stopping of motion; in conclusion the paper presents a representation of steady-state solution in terms of superposition of the waves produces by “elementary fractures”.